Topical Glucose Induces Claudin-1 and Filaggrin Expression in a Mouse Model of Atopic Dermatitis and in Keratinocyte Culture, Exerting Anti-inflammatory Effects by Repairing Skin Barrier Function - Kiyoko Yamada; Kenji Matsushita; Jingshu Wang; Takuro Kanekura (Medical Journals Sweden, 2017)
Atopic dermatitis (AD) is a chronic inflammatory skin disease. Corticosteroids, which are widely used for AD treatment, have adverse effects, and alternative treatments are urgently needed. This study examined the effect of topical application of high-dose glucose on inflamed skin in a murine model of AD. High-dose glucose treatment on the ear reduced dermatitis scores and ear thicknesses in mite antigen-treated NC/Nga mice. The levels of thymus and activation-regulated chemokine (TARC), Th cytokines (interleukin (IL)-4, IL-5, IL-12, IL-13, and (interferon) IFN-γ), and IgE were decreased in the serum of high-dose glucose-treated mice. Expression of claudin-1 and filaggrin was reduced in the ear epithelium in the NC/Nga mice. However, the reduced expression was restored by topical treatment with high-dose glucose. High-dose glucose also induced the expression of claudin-1 and filaggrin in cultured human skin keratinocytes. Co-stimulation with IL-4, IL-13, and thymic stromal lymphoprotein downregulated the expression of filaggrin in culture. However, high-dose glucose treatment restored the reduced expression of filaggrin. These results suggest that high-dose glucose treatment suppresses inflammation in the skin lesions by improving the skin barrier function.